2020
DOI: 10.1155/2020/8040517
|View full text |Cite
|
Sign up to set email alerts
|

Properties of 3D Printable Poly(lactic acid)/Poly(butylene adipate-co-terephthalate) Blends and Nano Talc Composites

Abstract: Biodegradable poly(lactic acid) (PLA) filaments have been widely used in the fused deposition modeling (FDM) 3D printing technology. However, PLA has low toughness and low thermal resistance that affects printability and restricts its industrial applications. In this study, PLA was compounded with 0 to 40 wt% of poly(butylene adipate-co-terephthalate) (PBAT) and varied content of nano talc at 0 to 40 wt% in a twin screw extruder. The compounds were reextruded to filaments using a capillary rheometer. PLA/PBAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 46 publications
0
43
0
Order By: Relevance
“…As shown in Figure 2 c, the cold crystallization disappeared after the second heating and revealed double melting peaks of the PLA matrix in the blend composites. It was considered that the addition of PBAT, PBS, and nano talc enhanced PLA crystallization and affected the recrystallization and remelting of PLA crystal in the composites [ 22 , 28 ]. Therefore, the incorporation of PBS enhanced the degree of crystallinity of 70/0/30/10 and 70/10/20/10 composite 3D prints, which should improve the heat resistance and mechanical properties of the binary and ternary blend composites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 2 c, the cold crystallization disappeared after the second heating and revealed double melting peaks of the PLA matrix in the blend composites. It was considered that the addition of PBAT, PBS, and nano talc enhanced PLA crystallization and affected the recrystallization and remelting of PLA crystal in the composites [ 22 , 28 ]. Therefore, the incorporation of PBS enhanced the degree of crystallinity of 70/0/30/10 and 70/10/20/10 composite 3D prints, which should improve the heat resistance and mechanical properties of the binary and ternary blend composites.…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that blending with ductile polymers, i.e., poly(butylene adipate-co-terephthalate) (PBAT), poly(butylene succinate) (PBS), polycaprolactone (PCL) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], and incorporating with particulate fillers and reinforcing fibers [ 25 , 26 , 27 , 28 , 29 ], can improve the limitations of PLA. From our previous study, the binary blend composites from PLA and PBAT blends (PLA/PBAT) and composites with nano talc (PLA/PBAT/nano talc) at 70/30/0/10 exhibited good toughness and printability, and can be presented as alternative filaments in FDM 3D printing [ 28 ]. Nevertheless, interlayer adhesion, anisotropy, and heat resistance should be developed for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…Lower layer height provides good mechanical strength. As the layer height decreases, the bonding between the layers is strengthened and results in an improved mechanical performance [ 36 , 44 ]. A similar effect is observed for the infill percentage (the quantity of build material), where the mechanical strength improves with an increase in material density [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…It melts between 180 to 200 °C, depending on other material added to it for color and texture. The important material properties of PLA are given in Table 1 [ 36 , 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…The final step (sintering) densifies the part by a thermal treatment that combines the powder particles. Two existing technologies—metal injection molding (MIM) [ 29 , 30 , 31 ] and FDM [ 32 , 33 , 34 ]—have been combined into an FDMet process. MIM is a powder metallurgical process that sinters metal particles at a temperature well below their melting point, thereby conserving heat energy.…”
Section: Introductionmentioning
confidence: 99%